Myeloma cells regulate miRNA transfer from fibroblast‐derived exosomes by expression of lncRNAs. Issue 4 (21st January 2022) - Saltarella, Ilaria; Lamanuzzi, Aurelia; Desantis, Vanessa; Di Marzo, Lucia; Melaccio, Assunta; Curci, Paola; Annese, Tiziana; Nico, Beatrice; Solimando, Antonio Giovanni; Bartoli, Giulia; Tolomeo, Doron; Storlazzi, Clelia Tiziana; et al.
Abstract: Multiple myeloma (MM) progression and drug resistance depend on the crosstalk between MM cells and bone marrow (BM) fibroblasts (FBs). During monoclonal gammopathy of undetermined significance (MGUS) to MM transition, MM cell‐derived exosomes (EXOs) reprogram the miRNA (miR) profile of FBs, inducing the overexpression miR‐23b‐3p, miR‐27b‐3p, miR‐125b‐5p, miR‐214‐3p, and miR‐5100. Here, we demonstrate that the miR content of MM FB‐derived EXOs (FB‐EXOs) overlaps the miR profile of parental FBs by overexpressing comparable levels of miR‐23b‐3p, miR‐27b‐3p, miR‐125b‐5p, miR‐214‐3p, and miR‐5100. Recipient MM cells co‐cultured with MM FB‐EXOs selectively overexpress only miR‐214‐3p and miR‐5100 but not miR‐23b‐3p, miR‐27b‐3p, and miR‐125b‐5p, suggesting a putative selective transfer. MM cells express HOTAIR, TOB1‐AS1, and MALAT1 lncRNAs. Transient transfection of MM cells with lnc·siRNAs demonstrates that HOTAIR, TOB1‐AS1, and MALAT1 lncRNAs are sponges for miR‐23b‐3p, miR‐27b‐3p, and miR‐125b‐5p. Indeed, lncRNA knockdown significantly increased miR levels in U266 MM cells co‐cultured with MM FB‐EXOs. Selective miR‐214‐3p and miR‐5100 overexpression modulates MAPK, PI3K/AKT/mTOR, and p53 pathways in MM cells. Interrogation using the DIANA tools algorithm and transient overexpression using miR mimic probes confirmed the involvement of miR‐214‐3p and miR‐5100 and their target genes, PTEN and DUSP16, respectively, in the modulation of these intracellular pathways. Finally, the uptake of EXOs as well as miR‐214‐3p and miR‐5100 overexpression increase MM cell proliferation and resistance to bortezomib‐induced apoptosis by switching the balance between pro‐/anti‐apoptotic proteins. Overall, these data show that MM cells are not simply a container into which EXOs empty their cargo. On the contrary, tumour cells finely neutralize exosomal miRs via lncRNA expression to ensure their survival. © 2021 The Pathological Society of Great Britain and Ireland.